Comparison of testicular cell population indexes in normal dogs using fine needle aspiration and imprint techniques - Kamali, Arash (2014)
Testicular cell population indexes have been described in human and a few domestic species of animals to evaluate spermatogenesis. Fine needle aspiration (FNA) and imprints are different techniques available to obtain specimens for cytological evaluation of the testicle. FNA is the less invasive method compared to the imprint. This study was conducted to determine and compare testicular cell population indexes using FNA and imprint methods among dogs of different age groups. A total number of 35 mixed breed dogs, with no testicular abnormalities were categorized into four different age groups; junior (0.5 - <2 years; N=7), adult (2 - <4.5 years; N=10), mature (4.5 - <7 years; N=11) and senior (7 - <10 years; N=7). Three FNA samples and two imprints were obtained from different but consistent locations of each testicle. Cytological evaluation was performed after staining with Wright’s stain 500 cells from each slide. The results of this study demonstrated no significant differences between the three different FNA locations or the two imprint areas. There were also no significant differences in the testicular cell population indexes between the left and right testicles in either of the techniques. Therefore, regardless of the sampling site, the same reference range of testicular cell population indexes can be used for interpretation. The mean of the testicular cell population indexes for FNA versus imprint samples are as follow: sperm index (SI): 40.54 vs. 23.11, Sertoli cell index (SEI): 8.83 vs. 5.11,Sperm-Sertoli cell index (SSEI): 7.20 vs. 6.69, late spermatid index (LSI): 33.55 vs. 27,early spermatid index (ESI): 23.09 vs.42.77 and spermatocyte index (SPI): 2.61 vs.7.08.All testicular cell population indexes were significantly (P< 0.05) different between FNA and imprints, except for SSEI. FNA samples consisted of more Sertoli cells and mature spermatogenic cells such as spermatozoa (SI: 40.54 ± 13.36 vs. 23.11 ± 10.88) and late spermatids while imprints contained early spermatids the most. Therefore, for interpretation of the samples, it is highly recommended to choose the reference range of the cell population indexes according to the sampling technique. Another important factor to be considered is the age of the animal. This is because of the significant differences between testicular cell indexes in different age groups. Based on FNA results, in the junior group, SI and SSEI were significantly lower and SEI and ESI were significantly higher than the mature group. However, the differences of the testicular cell indexes were not so remarkable in imprint samples, except for a higher SEI in junior group compared to the other groups. The results of this study suggest that FNA is a more useful technique compared to imprint, as it is less invasive and more efficient in detection of spermatozoa and Sertoli cells. Beside that, the age of a dog should be taken into consideration, whenever FNA based testicular cell population indexes are to be interpreted.